The effect of two proposed training curricula using pregnancy time and repetition on a number of physical, motor and skill variables for volleyball players - khudhur, Rizgar (Humanities Journal of University of Zakho, 2021)
The study aims to: Detecting the effect of the training curriculum using the method of controlling the duration of pregnancy and repetition on some variables (physical, motor and skill) for young volleyball players. Detecting the effect of the training curriculum using the method of controlling the number of repetitions in some variables (physical, motor and skill) for young volleyball players. Detecting the effect of the training curriculum using the method of controlling the duration of pregnancy on some variables (physical, motor and skill) for young volleyball players. The research community was chosen in a deliberate way, represented by young volleyball players from Koya Sports Club in Erbil governorate in volleyball for the sports season (2019-2020), As for the research sample, it was chosen in a deliberate way, as they represent (71.42%) of the research community of (28) players, and this sample was divided into two experimental groups of (10) players for each group by making a lottery, 8 players were excluded due to their participation in the exploratory experiment, the injured and the failure to train, and the method used was the experimental method, A number of tools and means were used to collect data, and after obtaining the results, they were discussed in a scientific manner supported by the sources to achieve the objectives of the research. In light of the research results, the researcher reached the following conclusions: The method of controlling the duration of pregnancy had a positive effect on physical and motor variables. The method of controlling the duration of pregnancy had a positive effect on the skill variables under study. The method of controlling the recurrence of pregnancy had a positive effect on the physical and motor variables. The method of controlling the recurrence of pregnancy had a positive effect on the skill variables under study.